LANGUAGE ERROR ANALYSIS IN THE DESCRIPTION COLUMN OF YOUTUBE RIA SW EPISODE DAEGU AND HONGKONG - Radita Rahmawati; Rizka Maulidania; Salsabila Putri Rahmawati; Aveny Septi Astriani (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to describe language errors on the Ria SW Youtube account. The type of research conducted is qualitative research using descriptive methods. The data source used is the description column on Ria SW's Youtube uploads of Hello Daegu 1, Hello Daegu 2, and Menggila Di Hong Kong 1. The data in this study are words that have language errors, be it phonological, morphological, syntactic, and semantic errors. Data collection techniques are carried out by the method of listening, reading, recording and literature study.